2007
DOI: 10.1303/aez.2007.173
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of sexual difference in dispersal strategy sensitive to population density

Abstract: Empirical studies reveal that dispersal behavior is dependent on local population density in different wild animals. Theoretical studies also pay much attention to modeling dispersal strategies sensitive to population density; however, the evolution of sex-biased dispersal has not been analyzed sufficiently by a model considering density-dependent dispersal. Therefore, a previous model where it is assumed that only genetic factors determine an individual's dispersal timing was thoroughly modified. The resultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…It follows that a male would benefit from leaving if they can assess that they are in a male‐surplus patch, which is in line with the findings of Hirota (2007). But it is a more exciting finding that the male would also benefit, on average, if he leaves regardless of such information (Fig.…”
Section: Model 1 the Potential For Coevolutionsupporting
confidence: 68%
See 1 more Smart Citation
“…It follows that a male would benefit from leaving if they can assess that they are in a male‐surplus patch, which is in line with the findings of Hirota (2007). But it is a more exciting finding that the male would also benefit, on average, if he leaves regardless of such information (Fig.…”
Section: Model 1 the Potential For Coevolutionsupporting
confidence: 68%
“…To our knowledge only four models on the evolution of sex‐specific dispersal have included variation in local sex ratio. Hirota (2007) compared the evolution of sex‐specific dispersal strategies when dispersal was conditional on either local density or sex ratio, and found that sex‐specific timing of dispersal evolved differently depending on which of these two cues was used by individuals as a trigger of dispersal. Thus individual sex‐specific responses to the local sex ratio can alter the course of dispersal evolution from what would be predicted by responses to demographic stochasticity that do not differentiate between males and females.…”
mentioning
confidence: 99%
“…First, males do not only "potentially eat something" -in many species they are the larger sex, which comes with a greater potential to deplete local resources (Clutton-Brock and Harvey, 1978;Boyd et al, 1994;Rankin and Kokko, 2007;Kawatsu, 2018). Second, the timing of dispersal is an understudied factor in dispersal evolution; for rare exceptions in an insect mating context, see Hirota (2005Hirota ( , 2007. The relative timing of density regulation is known to alter predictions of dispersal rates (Sasaki and de Jong, 1999;Ravigné et al, 2004;Débarre and Gandon, 2011;Massol and Débarre, 2015), but we are not aware of a model that would expand on the logic that the timing of dispersal, not merely the occurrence (disperse vs. philopatry) of it, can evolve via kin selection.…”
Section: Introductionmentioning
confidence: 99%
“…Together with previous studies (Hiura, 1968, 1974; Ejima, 1987; Obara & Majerus, 2000) these findings suggest that P. rapae is of European origin and that a small number of individuals entered Asia and expanded rapidly in a relatively recent time. Particularly, long‐distance dispersal by females contributes to the sharing of a maternal inherited marker among populations (Hirota, 2004, 2005, 2007). Because the sequence of the ND5 region of the New Zealand population coincides completely with the population found in Bonn, Europe, the results presented here indicate that the New Zealand population descended from a European subspecies that was artificially introduced to New Zealand.…”
Section: Discussionmentioning
confidence: 99%